The COVID-19 pandemic in Binmaley changes in spaces, experience of religion, and faith expressions - Diaz, Rizelle A.
This thesis analyzes how COVID-19 public guidelines have affected people's experience of religion. It looks into the changes in the space, territory, and faith expressions of the parish church community in Binmaley, Pangasinan. Through these three concepts, the thesis recognizes the parish as thirdspace. Edward Soja's (1996, p.73) thirdspace asserts that "we are ... historical-social-spatial beings, actively participating individually and collectively in the construction/production - "The becoming" - of histories, geographies, societies. Interpreting Soja's (1996, P. 71) thirdspace, the trialectic of spatiality-historically-sociality, the study denotes spatiality as space, historicality as memory, and sociality as faith expressions.